AIS Usage Factors and Impact among Jordanian SMEs: The Moderating Effect of Environmental Uncertainty - Lutfi, Abd Alwali; Md Idris, Kamil; Mohamad, Rosli (Journal of Advanced Research in Business and Management Studies, 2020)
Small and medium Enterprises (SMEs) are struggling to survive in the present competitive environment. Accounting Information Systems (AIS) has great potentials to facilitate firms in attaining sustainable competitiveness and to survive in such environment. Nevertheless, the use of AIS among Jordanian SMEs has been reported as relatively low, which in turn does not affect SMEs effectively. Drawing upon Technology-Organization-Environment (TOE) framework as well as the ResourceBased View (RBV) theory, authors proposed an integrated model to examine the antecedents and impact of AIS usage in Jordanian SMEs. The proposed model enables incorporation of usage and the performance aspects of AIS in a single model. This study employed self-administered questionnaire survey for data collection purpose. The research model was validated based on the responses from 186 Jordanian SMEs. There are three major findings being observed from this study. First, competitive pressure, compatibility, organizational readiness, owner/manager commitment and government support are found to significantly influence the usage of AIS. Secondly, the study demonstrates significant and positive relationship between AIS Usage and AIS Effectiveness. Finally, contrary to the expectation, environmental uncertainty does not moderate the relationship between AIS usage and AIS effectiveness. The findings provide insights as how firms could improve their AIS usage for better firm performance. The current paper also contributes to the small but emergent stream of literature that examines antecedents and impact of IS/IT usage.